Prognostic value of MRI‐determined cervical lymph node size in nasopharyngeal carcinoma - Cheng‐Long Huang; Yang Chen; Rui Guo; Yan‐Ping Mao; Cheng Xu; Li Tian; Li‐Zhi Liu; Ai‐Hua Lin; Ying Sun; Jun Ma; Ling‐long Tang (Cancer Medicine, 2020)
Abstract Objectives To investigate the prognostic value of magnetic resonance imaging (MRI)‐determined cervical lymph node (CLN) size in nasopharyngeal carcinoma (NPC). Methods We retrospectively reviewed 2066 patients with NPC treated with intensity‐modulated radiotherapy, and randomly divided them into two groups, in a 1:1 ratio. One group was used for training (the training group), and the other one was for internal validation (the validation group). All patients had undergone MRI examination and the maximal axial diameters (MAD) of the axial plane of all positive nodes had been measured and recorded. Results Of 683 patients with CLN metastases in the training group (n = 1033), MAD = 4 cm was associated with worse OS (64.7% vs 84.6%, P < .001), DFS (55.9% vs 76.3%, P = .001), and DMFS (67.6% vs 86.1%, P = .001). Multivariate analysis showed that MAD = 4 cm was a significant negative prognostic factor for OS (HR = 2.058; P = .025), DFS (HR = 1.727; P = .049), and DMFS (HR = 2.034; P = .036). When MRI‐determined MAD = 4 cm was classified as N3 in the N classification, the OS, DFS, DMFS, and RRFS survival curves were well separated. The OS, DFS, DMFS, and RRFS concordance indexes were not statistically different between the proposed N staging system and the UICC/AJCC staging system in the training group, or between the training group and the validation group (all P = .05). Conclusion MAD = 4 cm on axial MRI slices can be recommended as a prognostic factor in future versions of the UICC/AJCC NPC staging system.